2009
DOI: 10.1002/prca.200900066
|View full text |Cite
|
Sign up to set email alerts
|

Differential protein expression between normal, early‐stage, and late‐stage myxomatous mitral valves from dogs

Abstract: Valvular heart disease accounts for over 20 000 deaths and 90 000 hospitalizations yearly in the United States. Myxomatous valve disease (MVD) is the most common disease of the mitral valve in humans and dogs. MVD is pathologically identical in these species and its pathogenesis is poorly understood. The objectives of this study were to (i) develop proteomic methodology suitable for analysis of extracellular matrix-rich heart valve tissues and (ii) survey over- and under-expressed proteins that could provide m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 18 publications
3
19
0
4
Order By: Relevance
“…Nevertheless, the role of CHAD and KERA in the mitral valve is unknown. In a canine MMVD proteomic study, decorin and biglycan were found to be up-regulated at the early stage of MMVD, but down-regulated at the late stage (Lacerda et al, 2009). In contrast in human MMVD, biglycan (protein), decorin (both mRNA and protein), and versican (protein) were found more abundantly expressed compared with normal mitral valves (Radermecker et al, 2003;Gupta et al, 2009).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Nevertheless, the role of CHAD and KERA in the mitral valve is unknown. In a canine MMVD proteomic study, decorin and biglycan were found to be up-regulated at the early stage of MMVD, but down-regulated at the late stage (Lacerda et al, 2009). In contrast in human MMVD, biglycan (protein), decorin (both mRNA and protein), and versican (protein) were found more abundantly expressed compared with normal mitral valves (Radermecker et al, 2003;Gupta et al, 2009).…”
Section: Discussionmentioning
confidence: 96%
“…Myxomatous mitral valve disease (MMVD) is the single most common acquired heart disease of the dog and is characterised by endothelial damage, stromal matrix degeneration, interstitial cell proliferation in the sub-endothelial zone and interstitial cell phenotypic changes (Buchanan, 1977;Beardow and Buchanan, 1993;Corcoran et al, 2004;Black et al, 2005;Disatian et al, 2008;Han et al, 2008;Lacerda et al, 2009;Borgarelli and Buchanan, 2012). The end-stage disease results in significant mitral regurgitation that can lead to left-sided congestive heart failure (Häggström et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several proteoglycans (e.g., decorin, biglycan, and mimecan) and cell adhesion proteins (e.g., versican, talin, and fibronectin) were found to be regulated in degenerated canine mitral valves, which suggests that extracellular remodeling occurs in the course of myxomatous transformation . Decorin, biglycan, and versican have also been associated with remodeling of other matrix components in myxomatous human mitral valves .…”
Section: Resultsmentioning
confidence: 95%
“…Thus this proteome database would contribute to a better understanding of the underlying disease biology, and may provide new insights for the diagnosis and therapy of DMVD. associated with valve degeneration in dogs [6], but to our knowledge, studies on the human mitral valve proteome have not been published. In part, the immediate procurement and preservation of mitral valve tissue during corrective mitral surgery poses logistical challenges and tissue samples have become less available as conservative surgery is increasingly adopted [7,8].…”
Section: Significance Of the Studymentioning
confidence: 99%